PERAN RECRUTMEN DALAM MENGHASILKAN SUMBER DAYA MANUSIA BERKUALITAS PADA ERA REVOLUSI INDUSTRI 4.0 - Hari Sucahyowati (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2020)
Globalization has entered a new era called the Industrial Revolution 4.0. Klaus (Shwab, 2016) through The Fourth Industrial Revolution states that the world has experienced four stages of revolution, namely: 1) Industrial Revolution 1.0 occurred in the 18th century through the invention of steam engines, so that goods could be mass produced, 2) Industrial Revolution 2.0 occurred in the 19th to 20th centuries through the use of electricity which made production costs cheap, 3) the Industrial Revolution 3.0 occurred around the 1970s through the use of computerization, and 4) the Industrial Revolution 4.0 itself occurred around the 2010s through intelligence engineering and the internet of things as the backbone of the movement and connectivity of humans and machines. The Industrial Revolution 4.0 has changed the way humans think, live and relate to one another. Significant changes in the field of technology, but also other fields such as economics, social, and politics. In this case also affects human resources (HR), because human resource is one of the success factors of the role of industry 4.0. Improving the quality of human resources is very important especially because Indonesia is still lacking, let alone utilizing the latest technology. Technological sophistication cannot be negotiated in social life, especially in the business world, and needs to be addressed carefully and on target. Because of the importance of preparing human resources to have talent and skills.